HIV and Cocaine Impact Glial Metabolism: Energy Sensor AMP-activated protein kinase Role in Mitochondrial Biogenesis and Epigenetic Remodeling - Samikkannu, Thangavel (Sci Rep, 2016)
HIV infection and cocaine use have been identified as risk factors for triggering neuronal dysfunction. In the central nervous system (CNS), energy resource and metabolic function are regulated by astroglia. Glia is the major reservoir of HIV infection and disease progression in CNS. However, the role of cocaine in accelerating HIV associated energy deficit and its impact on neuronal dysfunction has not been elucidated yet. The aim of this study is to elucidate the molecular mechanism of HIV associated neuropathogenesis in cocaine abuse and how it accelerates the energy sensor AMPKs and its subsequent effect on mitochondrial oxidative phosphorylation (OXPHOS), BRSKs, CDC25B/C, MAP/Tau, Wee1 and epigenetics remodeling complex SWI/SNF. Results showed that cocaine exposure during HIV infection significantly increased the level of p24, reactive oxygen species (ROS), ATP-utilization and upregulated energy sensor AMPKs, CDC25B/C, MAP/Tau and Wee1 protein expression. Increased ROS production subsequently inhibits OCR/ECAR ratio and OXPHOS, and eventually upregulate epigenetics remodeling complex SWI/SNF in CHME-5 cells. These results suggest that HIV infection induced energy deficit and metabolic dysfunction is accelerated by cocaine inducing energy sensor AMPKs, mitochondrial biogenesis and chromatin remodeling complex SWI/SNF activation, which may lead to neuroAIDS disease progression.